Risco de desenvolvimento e responsabilidade civil: a responsabilização dos fornecedores de alimentos quimicamente manipulados e geneticamente modificados na perspectiva do biodireito - Pereira, Henrique Mioranza Koppe (Universidade do Vale do Rio do Sinos, 2008)
The present dissertation has the main point the discussion the genetic modified and chemistry manipulated food supplier accountability by risks and damages to health and life of the consumer in development risk cases, because the Brazilian Consumers Law hasn’t clear provisions about these question. Using how theoretical reference, for this work, the risk society theory of Ulrich Beck, that shows the risk contest that finds the production in the food industry. Since this studies about Biolaw and Bioethic, will search argumentations that present possibilities so that juridical systems act to the protection of the human health and life. After these consideration, will realize that, beyond a fragility and the vulnerability of life, it’s not possible the civil accountability exclusion to the food suppliers, based in the development risk
Keywords: alimentos geneticamente modificados; alimentos quimicamente manipulados; bioética; responsabilidade civil; risco de desenvolvimento; biodireito; bioethics; chemistry manipulated food; civil accountability; development risk; genetic modified food; biolaw; Ciências Sociais Aplicadas